Antiretroviral Treatment-Associated Tuberculosis in a Prospective Cohort of HIV-Infected Patients Starting ART - William Worodria; Marguerite Massinga-Loembe; Harriet Mayanja-Kizza; Jane Namaganda; Andrew Kambugu; Yukari C. Manabe; Luc Kestens; Robert Colebunders (Clinical and Developmental Immunology)
Commencement of antiretroviral treatment (ART) in severely immunosuppressed HIV-infected persons is associated with unmasking of subclinical disease. The subset of patients that are diagnosed with tuberculosis (TB) disease while on ART have been classified as ART-associated TB. Few studies have reported the incidence of ART-associated TB and unmasking TB-IRIS according to the International Network for the Study of HIV-Associated IRIS (INSHI) consensus definition. To determine the incidence and predictors of ART-associated TB, we screened 219 patients commencing ART at the Infectious Diseases Clinic in Kampala, Uganda for TB by symptoms, sputum microscopy, and chest X-rays and followed them for one year. Fourteen (6.4%) patients were diagnosed with TB during followup. Eight (3.8%) patients had ART-associated TB (incidence rate of 4.3 per 100 person years); of these, three patients fulfilled INSHI criteria for unmasking TB-associated IRIS (incidence rate of 1.6 per 100 person years). A body mass index of less than 18.5 kg/m2 BMI (HR 5.85 95% CI 1.24–27.46, P=.025) and a C-reactive protein greater than 5 mg/L (HR 8.23 95% CI 1.36–38.33, P=.020) were risk factors for ART-associated TB at multivariate analysis. In conclusion, with systematic TB screening (including culture and chest X-ray), the incidence of ART-associated TB is relatively low in settings with high HIV and TB prevalence.